Pediatric neurology and telehealth before and during SARS-CoV-2 pandemic - Golebiowska, Beata; Golebiowska, Maria (Journal of Education, Health and Sport, 2021)
Telehealth has been known in medicine for over 70 years. Until the year 2020 it has been utilized in a limited setting to provide long-distance care for individuals residing in areas lacking health facilities. SARS-CoV-2 pandemic shifted the priorities of healthcare system towards COVID-19 infections, which resulted in the transition of non-emergency consultations to telemedicine in many countries. Since pediatric neurology requires frequent follow-up and multidisciplinary care, the purpose of our work is to determine the spectrum of use of telehealth in pediatric neurology before and during the pandemic. Secondly, we would like to discuss the differences of focus in tele-neurology for children patients between the pre-pandemic and during pandemic timeframes. Within 171 articles of PubMED database, 36 substantial articles on the introduction of telehealth to pediatric neurology were included in the review. 30.5% of the articles have included the implementation of telemedicine before the pandemic, 69.5% of the articles discussed improvements made after the pandemic started. The spectrum of disorders and interventions considered for telehealth included epilepsy, cerebral palsy, rare diseases, teleneuropsychology and teleneurorehabilitation. Among major differences between pre-pandemic and pandemic research, increase in international cooperation and discussion of not only medical, but also scientific and academic impact of the pandemic could be noted. Telehealth offers sustainable alternatives to many interventions which cannot be performed in-person during public health emergency such as SARS-CoV-2 pandemic. Despite high satisfaction of caregivers and healthcare professionals from the virtual visits, solutions are still far from perfection and need improvements to provide more support for the patients with various disorders, cover the concerns of privacy and confidentiality, as well as support patients from low-income and lack of electronic techology backgrounds.